Spinoplastic Reconstruction Using Iliac Crest Vascularized Bone Graft following Sacral Ependymoma Resection - Edward M. Reece, MD; Nicole Van Spronsen, MD; Calogero Velluto, MD; Jonathan L. Jeger, MD; Christopher Fullmer, DO; Isra Abdulwadood, BS; Jenna Meyer, MD; Alexander E. Ropper, MD; Sebastian Winocour, MD; Michael A. Bohl, MD; Maziyar A. Kalani, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Sacral reconstruction post tumor resection has historically been executed with the placement of hardware or free tissue transfer. Reconstruction using a vascularized bone graft is an alternative that avoids the complications associated with hardware placement or free tissue transfer. This article describes the first documented case of spinoplastic reconstruction using an iliac crest vascularized bone graft (IC-VBG) after the resection of a sacral ependymoma. This is a case of a 17-year-old boy with a history of a sacral myxopapillary ependymoma. He presented to a local emergency department complaining of 6 months of urinary incontinence and progressive paresthesias affecting the left lower extremity. Magnetic resonance imaging was significant for a lesion located in the extradural spinal canal. Biopsy confirmed a myxopapillary ependymoma, World Health Organization grade II. The initial intervention involved tumor resection with titanium hardware placement. He subsequently required replacement of the titanium hardware with carbon fiber, secondary to the need for surveillance imaging. He underwent harvesting and inset of the IC-VBG at the time of hardware replacement. IC-VBG is a safe and effective modality for spinoplastic reconstruction. It enhances the potential for solid bony union and offers a practical alternative to free bone transfer. This approach provides an asset to add to a reconstructive surgeon’s armamentarium, making it an essential tool for reconstructive surgeons working in conjunction with spinal surgery colleagues.